ICE BREAKER: A STRATEGY TO ENHANCE STUDENT’S ABILITY IN SPEAKING OF ISLAMIC JUNIOR HIGH SCHOOL AT SAWIT SEBERANG, LANGKAT REGENCY - sholihatul hamidah daulay (IJET (Indonesian Journal of English Teaching), 2018)
This research was aimed to enhance students’ speaking skill at eight grade students of Islamic Junior High School Sawit Seberang, Langkat Regency. The subject of this research was a class consisted of 40 students. The research consisted of two cycles. Each cycles consisted of two meetings. The object of this research was to enhance students’ speaking skill by the use of Ice Breaker strategy. This research was conducted by using Classroom Action Research. Qualitative and Quantitative data were used in this research. The qualitative data while the quantitative data were taken from students’ score in Pre-Test, Post Test I, and Post-Test II. The result of analyzing data indicated that there was significance enhancement on students’ speaking skill after the use of Ice Breaker strategy. It can be seen from the students’ score in every cycle. In Pre-Test, there were only 30% (12 students) whose score up to 75. In Post-Test I, there was 52.5% on the percentage of students whose score up 75 (21 students), while in Post-Test II there were 80% students whose score up 75 (32 students). From data analysis, it showed that there was enhancement on students’ speaking skill. It can be seen from the mean of Post-Test II was 80.3. In other words, students’ speaking skill has enhanced. Based on the qualitative data, the students gave good responses and showed enthusiasm after the use of Ice Breaker strategy in speaking skill.